Analisis Dampak Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Jayasegar Berkat Mandiri Sunter - Muhamad Hafitz; Lukman Hakim; Iwan Supriyanto (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
The success of a company cannot be separated from its existence and the influence of human resources in it. Human resources can be interpreted as the integrated ability of the mind and physical power possessed by an individual. In a company, employees are one of the most important elements, because without the role of employees the company will not run, even though various factors needed are available. This study aims to determine the workload and work environment on employee performance at PT Jayasegar Berkat Mandiri Sunter. The sample in this study were employees who work at PT Jayasegar Berkat Mandiri Sunter. The method used in this study is the associative quantitative method by conducting multiple linear regression analysis tests. This research was conducted using a quantitative method. The data collection technique used was a questionnaire. The data analysis technique used in this study was multiple linear regression using the Spss. Workload partially does not affect employee performance, Work Environment partially has a significant effect on employee performance. Workload and Work Environment simultaneously affect employee performance. Workload and Work Environment can explain Employee Performance by 95%.